Dakwah Digital Media Sosial Penguatan Peran Keagamaan Ibu-ibu di Paguyuban Istri Peduli - Romlah; Riniyati; Sobirin (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
The development of social media has presented new opportunities for Islamic da'wah practices in the digital era, particularly in empowering women's associations as agents of strengthening religious values ​​at the village level. This community service activity aims to optimize the use of social media as a means of digital da'wah through creative training in the creation and dissemination of relevant and contextual religious content. The activity was carried out using a participatory approach through training and mentoring for women from the Caring Wives Association in Mekarjaya Village, Indramayu Regency, with data collected through observation, interviews, and post-training skills evaluation. The results of the activity showed significant improvements in digital literacy, self-confidence, and the active role of participants in producing and disseminating communicative and educational da'wah messages. Social media not only functions as a means of disseminating religious messages but also serves as a space for interaction that strengthens social solidarity and community religious awareness. These findings confirm that digital da'wah based on ongoing training and mentoring is an effective and adaptive strategy in building an inclusive, participatory religious community that is relevant to the dynamics of society in the digital era.